2008
DOI: 10.1111/j.1537-2995.2007.01599.x
|View full text |Cite
|
Sign up to set email alerts
|

A pool of repeat blood donors can be generated with little expense to the blood center in sub‐Saharan Africa

Abstract: It has been demonstrated that the use of a culturally and socially adapted environment to make the gift of blood a pleasurable and festive experience generated a new pool of blood donors spontaneously repeating donations. This program indicates that retaining Ghanaian blood donors is possible at little extra cost to the blood center and that such an approach may represent a substantial help in the efforts of sub-Saharan Africa to collect volunteer blood.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
62
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(74 citation statements)
references
References 9 publications
9
62
3
Order By: Relevance
“…In our study, the donor population was characterized by increased numbers of young donors who were in the age group of 18-25 years, with college level education, which was similar to the findings of the studies which were done by Allain et al, [7] and Hinrich et al, [8]. In contrast, Sampath et al, showed that 48.4% of the donors were in the age group of 26-50 years [9].…”
Section: Discussioncontrasting
confidence: 38%
“…In our study, the donor population was characterized by increased numbers of young donors who were in the age group of 18-25 years, with college level education, which was similar to the findings of the studies which were done by Allain et al, [7] and Hinrich et al, [8]. In contrast, Sampath et al, showed that 48.4% of the donors were in the age group of 26-50 years [9].…”
Section: Discussioncontrasting
confidence: 38%
“…In our study, the participants were young adults who were in the age group of 18-25 years, with college level education, which was similar to the findings of the studies done by Allain et al [7] and Hinrichs et al [8] In contrast, Sampath et al observed that 48.4% of the donors were in the age group of 26-50 years. [9] In our study, 51.5% said that blood can be donated every 6 months and 19.9% students knew correctly that the blood can be donated every 3 months.…”
Section: Discussionsupporting
confidence: 49%
“…In our study, the donor population was characterized by only 31% of the study population with higher secondary or above level education, which was a contrast to the findings of the studies which were done by Allain et al 10 , and Hinrich et al 11 . A study by Agarwal et al 8 found that while among illiterates 81 percent of the respondents knew about blood donation, among the post graduates the same ratio was found to be almost cent-percent.…”
Section: Fig 3: Distribution Of Study Population According To Their contrasting
confidence: 55%